Phylogenetic position and taxonomic assignment of Thlaspi aghricum P.H.Davis & K.Tan (Brassicaceae) - Fırat, Mehmet; Özüdoğru, Barış; Tarıkahya Hacıoğlu, Burcu; Bülbül, Ali Savaş; Al-Shehbaz, Ihsan Ali; Mummenhoff, Klaus (Phytotaxa, 2014)
A general review of the taxonomic status of Thlaspi past and present is given, and a critical evaluations of its segregates based on both morphological and molecular data are  presented. ITS molecular phylogenetic study of Thlaspi aghricum and related species, as well as seed-coat morphology and anatomy strongly support the placement of the species in Noccaea. The new combination N. aghrica is proposed, and detailed description and distribution of the species are given.